Ecoliteracy Competence Assessment to Improve Innovation Capability in a Rural Community - Kusumawardani, Erma; Nurmalasari, Yuli; Rofiq, Akhmad (Journal of Education Reseach and Evaluation, 2023)
Efforts to improve people's life skills are part of empowerment; however, many empowerment programs have not been fully utilized because they have failed to adapt to community needs. This phenomenon serves as the foundation for this study, which aims to analyze of community competencies centered on the ability to recognize potential and utilize the environment (ecoliteracy). A qualitative approach was used in this study, with an exploratory descriptive design. Interviews, observation, study documentation and focus group discussions were used to collect research data. 12 family representatives and 14 family facilitators provided data. Data analysis was carried out by each researcher by reading transcripts in an open coding process, looking for concepts, categories, characteristics, and dimensions that characterize each aspect found. The finding reveals that potential of the surrounding nature have awareness and knowledge of how to use ecological resources to sustain life, and are uneasy due to economic problems. Second, on an emotional level, they are satisfied when they see results from using the environment, realize the value of ecoliteracy for survival, and use the land for daily personal consumption. Third, in terms of land use and assistance programs as a source of income support the cost of living, taking into account economic aspects in meeting life's necessities. To sum up, he research results which are differentiated into three aspects, it shows that there is still a lot of potential that can be used as a basis for efforts to develop ecoliteracy learning models for the community